Transcriptomic Changes of Photoperiodic Response in the Hypothalamus Were Identified in Ovariectomized and Estradiol-Treated Sheep - He, Xiaoyun; Di, Ran; Guo, Xiaofei; Cao, Xiaohan; Zhou, Mei; Li, Xiaoyu; Xia, Qing; Wang, Xiangyu; Zhang, Jinlong; Zhang, Xiaosheng; Liu, Qiuyue; Chu, Mingxing (Frontiers in Molecular Biosciences, 2022)
Accurate timing of seasonal changes is an essential ability for an animal’s survival, and the change in photoperiod is the key factor affecting reproductive seasonality in mammals. Emerging evidence has suggested that multiple hypothalamic multiple genes participate in photoperiod-induced regulation of reproductive activities in sheep, but the mechanism is still unclear. In this study, we initially examined the plasma level of 2 major reproductive hormones, follicle-stimulating hormone (FSH) and prolactin (PRL) under different photoperiod in ovariectomized and estradiol-treated (OVX+E2) sheep using radioimmunoassay (RIA). Of the 2 hormones, the concentration of PRL significantly increased with the extension of the photoperiod, while FSH showed the opposite trend. Subsequently, examination of the transcriptomic variation between the short photoperiod (SP) and long photoperiod (LP) was conducted. Differential expression analysis and functional annotation showed that several key genes in the insulin secretion (VAMP2, PRKACB, PRKCG and PLCB1), GnRH (MAPK13, CGA, CDC42, ATF4 and LHB) pathways and circadian entrainment (KCNJ5, PER1, GNB2, MTNR1A and RASD1), as well as numerous lncRNAs, including XR_173257.3, XR_173415.3, XR_001435315.1, XR_001024596.2 and XR_001023464.2, were shown potentially vital for the hypothalamic photoperiodic response. Four of the differentially expressed mRNAs and lncRNAs were validated by qPCR. The constructed mRNA-mRNA interaction networks further revealed that transcripts potentially participated in hypothalamic thyroid hormone synthesis, endocrine resistance and neuroactive ligand-receptor interactions. the interactome analysis of lncRNAs and their targets implied that XR_173257.3 and its target arylalkylamine N-acetyltransferase (AANAT), XR_173415.3 and its target TH might participate in regulation of seasonal reproduction. Together, the changes in reproductive hormones and transcriptome will help to determine important photoperiod-induced lncRNAs and mRNAs, and provide a valuable resource for further research on reproductive seasonality in sheep.